Growth and photosynthetic capacity in two woody species of cerrado vegetation under different radiation availability - Carlos Cesar Ronquim; Carlos Henrique B. de A. Prado; Nádia Figueiredo de Paula (Brazilian Archives of Biology and Technology, 2003)
Seedlings of two woody species of cerrado vegetation, Copaifera langsdorffii and Eriotheca gracilipes, were studied under three different radiation availability (100, 80 and 30% transmittance). Full solar radiation brought about more biomass, higher total leaf area, higher maximal photosynthesis per crown on area or on mass bases and higher photosynthetic capacity on area bases. Only the photosynthetic capacity values on leaf mass bases were higher in both species under low radiation availability (80 and 30% transmittance). The differences of accumulated biomass appeared more clearly after 4 months of sowing but the root/shoot dry biomass ratio and height were maintained constant for both species independently of the available radiation. Cultivated under full solar radiation both species will be able to cover more suitable the two processes during seedling's phase: growth and defense. Duas espécies de cerrado (Copaifera langsdorffii e Eriotheca gracilipes) foram cultivadas sob três diferentes condições de radiação (100, 80 e 30% de transmitância). A radiação solar plena proporcionou as condições mais favoráveis para o desenvolvimento das espécies: maior acúmulo de biomassa total, maior área foliar total, maior fotossíntese potencial por copa expressa em área ou em massa e maior capacidade fotossintética expressa em área foliar. Somente os valores de capacidade fotossintética expressa em massa foram maiores sob baixa radiação (80 e 30% de transmitância) para ambas as espécies. As diferenças de biomassa acumulada apareceram mais claramente após os 4 meses de plantio, mas a relação massa seca raiz/parte aérea e a altura foram mantidas independentes da radiação disponível para ambas as espécies. Sob 100% de transmitância estas espécies apresentaram um balanço de carbono mais positivo e condições mais favoráveis para suprir as duas principais demandas neste estágio do ciclo de vida da planta: o crescimento e a defesa.